Southeast Asian Studies in Southeast Asia Agenda for the 21st Century - Ooi, Keat Gin (Universiti Sains Malaysia, 2006)
'Southeast Asian Studies' in contemporary Southeast Asia is assuming increasing importance in the region itself. Several institutions of higher learning in the region have study programs ranging from baccalaureate to doctorates. At the same time there are several centers with particular research interest in Southeast Asia as a region and/or focusing on certain geographical area.